Letter to Jane Tolmach from Charles Warren - Charles Warren:::::: (1968)
This February 20, 1968 letter from the California Democratic Presidential Delegation Committee informs Jane Tolmach that she has been recommended as one of the 174 voting members of the state's delegation to the 1968 Democratic National Convention. She is instructed to complete and return an Affidavit of Candidate for Delegate so it can be filed by the March 4 deadline. Although the delegation is described as technically uncommitted, members are expected to support President Lyndon B. Johnson. The letter notes that attending the convention will cost each delegate approximately $750. A postscript confirms that her signed affidavit has already been received and thanks her for her prompt response.